Selection in Europe–the Case of Greece - Gouvias, Dionysios (Education Policy Analysis Archives, 1998)
This article deals with inequality of access to higher education in Greece, and especially, the case of the Metropolitan Area of Athens. Specifically, I deal with a general overview of the debates about "selection" in the educational systems of Europe, with special reference to the case of Greece. It is argued here that in those levels of the educational "ladder" where the degree of specialisation and the need for individual selection is insignificant, inequalities exist, but are not profound. On the contrary, in the upper levels, and especially as the time to enter (or to be trained to enter) the labour market comes closer, students' success depends much more on externally assessed examination performance and, therefore, a more rigorous selection process emerges–a process that is decisively influenced by the labour- market requirements and limitations. Finally, an extended examination of the evolution of the Greek school-system and the changes in examination practices, and the relationship between the structure of the school system and the job-market, will be attempted.